Portraits of 21st Century Chinese Universities - Hayhoe, Ruth. author. aut Link
XVI, 488 p. 25 illus.
Keywords: This book examines the ways in which China’s universities have changed in the dramatic move to a mass stage which has unfolded since the late 1990s. Twelve universities in different regions of the country are portrayed through the eyes of their students, faculty and leaders. The book begins with the national level policy process around the move to mass higher education. This is followed by an analysis of the views of 2,300 students on the 12 campuses about how the changes have affected their learning experiences and civil society involvement. The 12 portraits in the next section are of three comprehensive universities, three education-related universities, three science and technology universities, and three newly emerging private universities. The final chapter sketches the contours of an emerging Chinese model of the university, and explores its connections to China’s longstanding scholarly traditions.